KUTAI KARTANEGARA DISTRICT LOCAL GOVERNMENT SUPERVISION ON PROSPEROUS RICE DISTRIBUTION IN MUARA WIS 2016 - Prabawa, Akbar (Advances in Social Sciences Research Journal, 2019)
Supervision is one of the basic management functions that is carried out so that group activities in implementing program performance are in accordance with the predetermined plans, including prosperous rice distribution in Muara Wis. Kutai Kartanegara District Local Government is required to be able to supervise the distribution of prosperous rice which is oriented towards the established standards, namely the right target, right price, right quality, right amount, on time, and right administration. This research focuses on the supervision process carried out by the Kutai Kartanegara District Local Government in distributing prosperous rice in Muara Wis. The results of the research found that Kutai Kartanegara District Local Government until now has not been able to optimize the supervising process of the distribution of prosperous rice in Muara Wis. This indicated that the existence of prosperous rice assistance that is not right on target for the people who need it because of the updated data. Moreover, the sense of the rice quality given for the community is very inappropriate, this happens at the stage of slow rice distribution to the community. Keyword: Supervision, Local Government, Prosperous Rice